2020
DOI: 10.1016/j.ijheatfluidflow.2020.108559
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform suction control of flow around a circular cylinder

Abstract: In the present study, numerical investigations were performed with optimisation to determine efficient nonuniform suction profiles to control the flow around a circular cylinder in the range of Reynolds numbers 4 < < 188.5. Several objectives were explored, namely the minimisation of: the separation angle, total drag, and the pressure drag. This was in an effort to determine the relationships between the characteristics of the uncontrolled flow and the parameters of optimised suction control. A variety of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This method of flow control has been studied widely during the 20 th Century, and continues to be investigated and developed today. One important finding from this research is that non-uniform suction profiles are usually much more efficient and effective than uniform or simple slot suction [2]. For example, optimisation studies where any profile of suction/blowing on the surface of a cylinder is permitted found the profiles that best reduced drag were non-uniform and distributed over the cylinder surface [3].…”
Section: Introductionmentioning
confidence: 86%
“…This method of flow control has been studied widely during the 20 th Century, and continues to be investigated and developed today. One important finding from this research is that non-uniform suction profiles are usually much more efficient and effective than uniform or simple slot suction [2]. For example, optimisation studies where any profile of suction/blowing on the surface of a cylinder is permitted found the profiles that best reduced drag were non-uniform and distributed over the cylinder surface [3].…”
Section: Introductionmentioning
confidence: 86%
“…The geometry for the numerical simulations can be found in Figure 1(a). The domain was based on that used by Wu et al for the numerical portion of their paper and has also been used successfully by the present authors [21,29]. The dimensions are dictated by the diameter of the cylinder, D = 0:1 m. Not visible in the figure is a circular curve with diameter 1:0002D concentric with the cylinder.…”
Section: Model and Numerical Methodsmentioning
confidence: 99%
“…This implies two important conclusions: (1) the location of the suction (angle of suction) is of critical importance in the effectiveness of control and (2) the control must be set up to account for this. Indeed, other investigations have verified the importance of the location of suction for delaying separation on the circular cylinder, including the fact that this is dependent on the Reynolds number [29]. Consequently, an ideal control that will be effective over a range of Re must be able to account for the changing location of optimal suction.…”
Section: International Journal Of Aerospace Engineeringmentioning
confidence: 97%
“…Maintenance of airway and improvement of oxygenation in patients are achievable through oral suctioning (Propp and Gillis, [38]). In fact, less invisible separation that do occur between the boundary layer can be eliminated by either nonuniform or uniform suction but non-uniform suction is more efficient; Ramsay et al [39]. In fluid dynamics, most especially analysis of boundary layer flows, this has led to the modeling of suction at the wall as v(x=0, y)=v w where v w is the suction velocity.…”
Section: Mathematical Formulationmentioning
confidence: 99%